Unveiling the Power of Fairness: Exploring Organizational Justice and Positive Behavior for Future Insights - El Qadri, Zainal Mustafa; Fuady, Misbach (JURNAL EKOBIS DEWANTARA, 2024)
This paper aims to focus on research configuration and to create a conceptual framework on the influence of salience oforganizational justice (OJ) dimension and salience of positive organizational behavior (POB) based on 5.530 articles from the Digital library. The method used in this study is a systematic review covering OJ and POB publications from the 2011up to 2019. This is the first paper to jointly analyze the influence of OJ and POB using systematic review method, which may enrich academic discussion. Findings: Distributive and procedural justice has the most weighted of evidence in influencing the salience of positive organizational behavior, followed by interpersonal and informational justice. While the highest sequences of salient outcome include organizational commitment, OCB, job satisfaction, organizational trust, job performance, and pay satisfaction. Interpersonal justice does not affect pay satisfaction, and informational justice only has salient outcome towards OCB, job performance, and pay satisfaction